The Impact of Music on Sports Activities: A Scoping Review - Majid Akhshabi; Mohammad Rahimi (Shahid Bahonar University of Kerman, 2021)
Generally, the music performances on sports activities are manifested and realized through the four mechanisms of reducing the feeling of tiredness, increasing excitement levels, creating harmony, and finally increasing calmness and the sense of comfort. This function becomes very important when considering that the music impact acts as a miracle doping in professional sports. Besides, the lack of enjoyment in sports activities is often mentioned as an obstacle to participation in sports activities. This article discussed, evaluated, and analyzed the research records in three main topics: 1. The benefits of music in sports activities, 2. The conceptual model for showing the different music impact in sports activities, and 3. The underlying mechanisms of music impact on sports. A scoping review of literature in sport and music field was conducted to fulfill the research objectives. Finally, the inference was made by proposing theories such as corresponding and induction of microscopic and macroscopic order along with another direct and secondary music impact. Researches have not been able to uncover all aspects of music magic secrets yet. So, this challenge remains for researchers and athletes on how to maximize the benefits of using music during sport and exercise by focusing on practical applied approaches.